Understanding diabetes - Aguinaldo, F. (MMA Publications, 2003)
Diabetes. Types of diabetes. Symptoms of diabetes. Managing diabetes. Treatment. How to control diabetes. Managing stress. Traveling with diabetes. Managing sick days. Test for managing diabetes. Considering pregnancy. It is a very brief and concise book yet provides all the essential information a diabetic person needs to know. It is also an effective guide to those who don't have the disease but are aware of getting it through family background.